IMPLEMENTASI PROJECT BASED LEARNING DALAM PENDAMPINGAN APLIKASI KEUANGAN BUMDES UNTUK MENINGKATKAN KOMPETENSI PENGELOLA BUMDES (STUDI PADA DESA KARANGPRING KECAMATAN SUKORAMBI KABUPATEN JEMBER) - Mohamad Nabil Tanzil Furqon; M Helmy Setyo Purwanto; Sigiet Rizky Fidiyanto; Tantri Maehap Sari; Fatihatur Rizqiyah; Adil Kristianto; Siska Aprilia Oktaviani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This devotion aims to improve the competence of Village-Owned Enterprises (BUMDes) Karangpring managers through mentoring the implementation of Microsoft Excel Macro VBA-based financial applications with a Project Based Learning approach. The main problem faced by BUMDes is the manual financial recording system which is inefficient, error-prone, and complicates the reporting process. The Participatory Action Research (PAR) approach is used to ensure the active involvement of BUMDes managers in all stages of activities, from problem identification to evaluation of application implementation. The results of the activity show that the use of Macro VBA-based applications can improve efficiency, accuracy, and transparency in preparing financial reports, as well as help managers understand financial performance more systematically.